On the visualization of hierarchical multivariate data - Zheng, Boyan; Sadlo, Filip (PacificVis 2021: Proceedings of the Pacific Visualization Symposium, 2021)
In this paper, we study the visual design of hierarchical multivariate data analysis. We focus on the extension of four hierarchical univariate concepts---the sunburst chart, the icicle plot, the circular treemap, and the bubble treemap---to the multivariate domain. Our study identifies several advantageous design variants, which we discuss with respect to previous approaches, and whose utility we evaluate with a user study and demonstrate for different analysis purposes and different types of data.